Assessment Standard for the International Classification of Functioning, Disability and Health Rehabilitation Set (Ⅱ) - Tiebin YAN; Yan GAO; Malan ZHANG; Liming YOU (康复学报)
For further utilization of the International Classification of Functioning, Disability and Health Rehabilitation Set, assessment standard for"the International Classification of Functioning, Disability and Health Rehabilitation Set"based on ICF classification was generated after repeatedly proving according to literature research, relevant fundamental principles and Chinese idiographic practical circumstances. The standard consists of 30 categories including 9 body functions,14 activities,7 participations. The standard describes detail of the basis of preparation, scope of application, composition of items, evaluation of results, criteria assessment, application under specific conditions, and precautions for use. It can be applied to evaluate the function of rehabilitation on patients, analyze rehabilitation needs and direct clinical practice.